A Study of Association of Toxoplasma gondii Infection With Schizophrenia in Mashhad Area, Khorasan Razavi Province, Iran - Bahareh Meftahi; Ebrahim Abdollahian; Ahmad Nematollahi; Gholamreza Razmi (International Journal of Epidemiologic Research, 2021)
Background and aims: Congenital toxoplasmosis is assumed to play a role in developing schizophrenia in human. This study aimed to estimate the relationship between Toxoplasma infection and schizophrenia by using enzyme-linked immunosorbent assay (ELISA) and polymerase chain reaction (PCR).   Methods: In this case-control study, 46 schizophrenic patients forming our case group as well as 40 healthy relatives of schizophrenic patients forming our control group were selected from among 456 inpatients with schizophrenia in Ibn Sina and Hejazi hospitals in Mashhad from June 2016 to February 2017. The blood samples from both groups were collected for serological and molecular tests. Different statistical methods such as Chi-square, independent t test, and logistic regression models were used in the present study.   Results: In the present study, the seroprevalence of T. gondii was 54% in case group and 45% in control (OR=1.44, 95% CI: 062- 3.40, P = 0.38). There was no significant association between the seroprevalence of T. gondii infection and age, gender, and season as the risk factors in the case group. Furthermore, a poor agreement was observed between the microscopy and PCR methods. Non-significant differences were found between the mean levels of interferon gamma (IFN-γ), C-reactive protein (CRP), and white blood cell (WBC) in two groups.   Conclusion: Contrary to the reports from some studies, no association was found between Toxoplasma infection and the schizophrenia. In order to better understand the effect of Toxoplasma on schizophrenia, it is necessary to develop laboratory methods to differentiate acquired toxoplasmosis from congenital one.